Orality Hermeneutics in the Gospel of Mark and the Timorese Natoni Tradition: A Comparative Library-Based Study - Yanjumseby Yeverson Manafe (DIEGESIS: Jurnal Teologi Kharismatika, 2026)
This article examines the dialogue between the oral traditions of the Timorese people and the Gospel of Mark through an oral-based hermeneutical approach, operationalized as a comparative library-based study rather than field ethnography. Primary data consist of the Markan text (Mark 4:1–34 and Mark 8:27–30); secondary data consist of published ethnographic documentation of Timorese oral practices, particularly natoni. Three analytical indicators are used consistently throughout the study: communal memory, speech event, and narrative performativity, synthesized from Walter J. Ong, Werner H. Kelber, James D. G. Dunn, Richard Bauman, Ruth Finnegan, Richard A. Horsley, and Dell Hymes. The analysis shows that both corpora exhibit structurally comparable oral mechanisms (repetition, dialogic address, and performative closure) that sustain memory and shape communal identity, without implying any historical or genealogical connection between them. The article positions its contribution against prior orality scholarship, particularly the volume Performing the Gospel, and argues that its distinct contribution lies in a documentary-comparative model applicable to library-based contextual hermeneutics where field access is constrained. The study concludes with an explicit call for future field-based validation of the proposed model. Abstrak Artikel ini mengkaji dialog antara tradisi lisan masyarakat Timor dan kesaksian Injil Markus melalui pendekatan hermeneutika berbasis orality, yang secara metodologis dioperasionalkan sebagai studi pustaka komparatif, bukan penelitian lapangan (etnografi partisipatoris). Data primer berupa teks Markus (Markus 4:1-34 dan Markus 8:27-30); data sekunder berupa dokumentasi etnografis terpublikasi mengenai praktik tutur masyarakat Timor, khususnya natoni. Penelitian menggunakan tiga indikator analisis secara konsisten di sepanjang naskah, yaitu memori komunal, peristiwa tutur (speech event), dan performativitas narasi, yang disintesiskan dari pemikiran Walter J. Ong, Werner H. Kelber, James D. G. Dunn, Richard Bauman, Ruth Finnegan, Richard A. Horsley, dan Dell Hymes. Analisis menunjukkan bahwa kedua korpus memperlihatkan mekanisme oral yang secara struktural dapat diperbandingkan (repetisi, sapaan dialogis, dan penutup performatif) yang berfungsi memelihara memori dan membentuk identitas komunal, tanpa mengandaikan hubungan historis maupun genealogis di antara keduanya. Artikel ini memosisikan kontribusinya berhadapan dengan kajian oralitas terdahulu, terutama volume Performing the Gospel, dan berargumen bahwa kebaruannya terletak pada model dokumenter-komparatif yang dapat diterapkan dalam hermeneutika kontekstual berbasis pustaka ketika akses lapangan tidak tersedia. Penelitian ini ditutup dengan seruan eksplisit bagi validasi lapangan pada penelitian lanjutan.